Physiological and performance effects of altitude training and exposure in elite athletes - Robertson, E. Y (2009)
Despite widespread popularity of altitude training with athletes and coaches, and extensive research over the last 50 years, the transfer of im provements in physiological capacities to competitive performance remains uncertain. This the sis quantified the magnitude of performance gains required to improve placing in in ternational competition, and the performance enhancements and physiological adaptati ons that can be obtained from altitude training and exposure in elite swimmers and runners. Performance gains of ~1% will substantially increase the chance of a medal in elite swimmers. This was quantified by a novel analysis of the relationships between lap time and performance, which combined between-athlete correlations and within-athlete effects. Overall, the final lap for 100-m events and the middle two laps for 200-m and 400-m events had the strongest relationship (r~0.7-0.9) with final time. A change in these laps was associated with ~0.4-0.8% improvement in final time for finalists, and ~0.5-1.1% for semi-finalists, depending on sex, stroke and event. However, a similar pattern of lap times was adopted in each event regardless of the sex, finish position, or the best and worst swims for an individual. To gain a competitive advantage, many athletes employ some form of altitude training in an attempt to elicit small enhancements in performance. Three to four repeated 2-wk blocks of living and training at natural altitude (1350 m) and/or simulated live high/train low exposure (LHTL, 2600 m, 9-10 h·d-1) were undertaken by elite swimmers (n=9). Each 2-wk block produced the following mean improvements: haemoglobin mass (Hbmass), 0.9% (±0.8%, 90% confidence limits); 4-mM lactate threshold velocity, 0.9% (±0.8%); 2-km time-trial performance, 1.2% (±1.6%). There was no substantial improvement in competition performance compared with swimmers (n=9) who received no altitude exposure (altitude-control: 0.5%; ±1.0%). To gain substantial enhancements in physiological and performance capacities, a more effective model of altitude training is required. The final two studies employed 3-wk bouts of simulated LHTL (3000 m, 14 h·d-1) in well-trained runners. The test-retest reliability of responses to 2 x 3-wk LHTL were quantified, with reproducible increases in Block 1 and 2 for V&O2max(2.1%; ±2.1% and 2.1%; ±3.9%) and Hbmass (2.8%; ±2.1% and 2.7%; ±1.8%), but 4.5-km time-trial performance was more variable (-1.4%; ±1.1%, faster and 0.7%; ±1.3%, slower) in the LHTL group (n=8). Compared with the control group (n=8) who had only trivial change s, the LHTL group were substantially faster after Block 1 (LHTL-control: -1.9%; ±1.8%), had higher Hbmass after Block 2 (4.2%;±2.1%), but a trivial difference in change in V&O2max after each 3-wk block. It appears that physiological responses to altitude are reproducible, but transfer to improved time-trial performance is more variable. Finally, the effect of 3 weeks of intermittent hypoxic training (TH, 2200 m, 4·wk-1) or combined LHTL plus TH (LH/TL+TH) were examined. The LH/TL+TH group (n=8) substantially improved V&O2max (4.8%; ±2.8%), Hbmass (3.6%; ±2.4%) and 3-km time-trial performance (-1.1%; ±1.0%); while the TH group (n=9 ) improved V&O2max (2.2%; ±1.8%), but had only trivial changes in Hb mass and time trial. The LH/TL+TH group had substantially higher Hb mass (4.3%; ±3.2%), however, the small increase in V&O2max (2.6%; ±3.2%) and trivial improvement in time trial performance (-0.9%; ±1.4%) became unclear when adjusted for differences in training (V&O2max: 0.8%; ±3.5% and time trial: -0.3%; ±1.5%). LH/TL+TH was a potent stimulator for improvements in physiological measures, but transfer of these improvements to time-trial performance was limited. A structured program of 3-wk simulated LHTL, with or without additional hypoxic training,can elicit substantial improvements in V&O2max and Hbmass and enhance time trial performance by ~1% in well-trained athletes. Evidence of individual responses indicates some athletes respond more favourably than others, and the degree of within-athlete variation to repeated bouts indicates altitude training should be managed carefully in the context of other training and competition. Altitude training and exposure can enhance physiological capacities, but further research is required to improve the direct transfer of these benefits to competitive performance.